Deciphering the complex interplay of waterlogging and anthracnose twister disease in onion (Allium cepa L.) - Salunkhe, Vanita N.; Adavi, Sandeep B.; Gawande, Suresh J.; Khapte, Pratapsingh S.; Gedam, Pranjali A.; Changan, Sushil S.; Reddy, K Sammi; Mahajan, Vijay (Frontiers in Plant Science, 2025)
In the face of the escalating crisis of climate change and global warming, agricultural crops face unprecedented challenges with the dual threat of abiotic and biotic stresses. Onion (Allium cepa L.), a crop of therapeutic and culinary value, is particularly vulnerable. Among the three seasons cultivated in India, which ranks first globally in total area and production, the monsoon season (July to October) onion production in India is significantly challenged by waterlogging and anthracnose disease caused by Colletotrichum gloeosporioides species complex. The projected changes in the climate, including erratic rainfall, may amplify the severity of these challenges, and their co-occurrence may pose a significant threat to sustainable onion production. To investigate this interaction, a pot experiment was carried out with a focus on evaluating how waterlogging timing, prior to (pre-infection) and following infection (post-infection), influences the disease establishment and their cumulative effect on plant performance. To evaluate this, we exposed 90-day-old onion plants to pre- and post-infection waterlogging, along with separate individual stresses and controls, which were grown without any stress, and various morpho-physio-biochemical parameters were recorded at two intervals (7 days after the first and secondary stress). We observed that plants receiving only an inoculum spray showed significantly higher plant height with enhanced pseudostem (51 cm), while waterlogging hindered it, with pre-infection waterlogging showing a 19% reduction. The post-infection waterlogging significantly suppressed the plant growth, reduced the chlorophyll and carotenoid content (nearly threefold), elevated the membrane injury, and displayed a notable decline in the relative water content (RWC) and protein content (69%–73%) compared to either individual or pre-infection waterlogging. Additionally, the post-infection waterlogging elicited a stronger antioxidant activity (SOD and APX), indicating more robust oxidative response. In contrast, the pre-infection waterlogging seemed to partially inhibit the pathogen establishment primarily due to hypoxia-induced plant defense response. These findings highlight the timing of the stress occurrence, with post-infection waterlogging exacerbating the disease progression, severity, and damage and pre-infection waterlogging offering partial tolerance. Understanding such a dynamic interaction will help in developing integrated management as well as developing a resilience onion cultivar to both biotic and abiotic stress through breeding strategies.